Learning, feedback from the teacher and peer-review: limits and potential - Valerio Ferro Allodola (Firenze University Press, 2020)
We went from an informative to a transformative culture of feedback; from a model in which the learner had a passive reception function (from the teacher to the learner), to one in which the learner is able to manage and self-regulate his own learning to improve it (communication between teacher and learner; peer-review), also with a view to preparing the learner for entry into a profession. This article aims to highlight the limits and potential of feedback and peer-review in the learning evaluation process, in the light of national and international research on the topic.   Apprendimento, feedback del docente e revisione tra pari: limiti e potenzialità Siamo passati da una cultura informativa a una cultura trasformativa del feedback; da un modello in cui il learner aveva una funzione di ricezione passiva (dal docente al discente), ad una in cui il learner è in grado di gestire e autoregolare il proprio apprendimento per migliorarlo (comunicazione tra docente e discente; revisione tra pari), in vista della preparazione al mondo delle professioni. Questo contributo intende evidenziare i limiti e le potenzialità del feedback e della revisione tra pari nel processo di valutazione dell'apprendimento, alla luce delle ricerche nazionali e internazionali sul tema.